2020
DOI: 10.1017/s0954422420000037
|View full text |Cite
|
Sign up to set email alerts
|

Early-life programming of adipose tissue

Abstract: Worldwide obesity is increasing at an alarming rate in children and adolescents, with the consequent emergence of co-morbidities. Moreover, the maternal environment during pregnancy plays an important role in obesity, contributing to transgenerational transmission of the same and metabolic dysfunction. White adipose tissue represents a prime target of metabolic programming induced by maternal milieu. In this article, we review adipose tissue physiology and development, as well as maternal influences during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 236 publications
(321 reference statements)
1
42
0
Order By: Relevance
“…Obesity in pregnancy is characterised by dyslipidemia, hyperleptinemia, hyperinsulinemia and a proinflammatory state, that may enhance adipogenesis and lipogenesis, resulting in higher white adipose tissue mass and adipocyte hypertrophy in offspring (157). Higher leptin levels were found in macrosomic newborns and are related to insulin levels and adiposity (158); this may explain how fetuses of obese mothers develop insulin-resistance in the womb and are born with higher adiposity (159).…”
Section: Obesity Overnutrition and Fetal Programmingmentioning
confidence: 99%
“…Obesity in pregnancy is characterised by dyslipidemia, hyperleptinemia, hyperinsulinemia and a proinflammatory state, that may enhance adipogenesis and lipogenesis, resulting in higher white adipose tissue mass and adipocyte hypertrophy in offspring (157). Higher leptin levels were found in macrosomic newborns and are related to insulin levels and adiposity (158); this may explain how fetuses of obese mothers develop insulin-resistance in the womb and are born with higher adiposity (159).…”
Section: Obesity Overnutrition and Fetal Programmingmentioning
confidence: 99%
“…After this initial period, there is a constant level of fat intake during the first 2 years, and ultimately increasing intake and oxidation of protein and carbohydrate [7]. Adipose tissue is an important target for nutritional, hormonal, and epigenetic signals to modulate fetal growth [8,9].…”
Section: Commentarymentioning
confidence: 99%
“…It is mandatory to know adipose tissue cells composition, distribution and action, together with adipose tissue development and relationship with fat free mass and bone mineral content. Specific and precise body composition assessment could explain the body weight regulation and the dis-regulation of the homeostatic system [4,8,10]. Unfortunately, all the measurements of body composition are indirect and we have limitations related to the intraindividual variability as a consequence of changes in fat free mass occurring with growth, maturation, and disease statues [9].…”
Section: Commentarymentioning
confidence: 99%
“…It is known that abnormal adipokine profile may be observed in obese children [15]. Moreover, it was suggested that impaired growth during critical periods, such as in the third trimester of pregnancy can lead the programming of adipose tissue, conferring a high subsequent cardiometabolic risk later in life [16]. In fact, an abnormal production of some adipokines was described in children with intrauterine growth restriction (IUGR) [17] who, in turn, may present an elevated risk of inflammatory chronic diseases [4,18].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, an abnormal production of some adipokines was described in children with intrauterine growth restriction (IUGR) [17] who, in turn, may present an elevated risk of inflammatory chronic diseases [4,18]. Similarly, an early postnatal environment with EUGR might be associated with a higher vulnerability to an adipose tissue disturbance [16]. However, there is scarce literature about the role of the antecedents of EUGR in the later adipokines status, although it could be similar to obesity or IUGR condition.…”
Section: Introductionmentioning
confidence: 99%